Pulsed 1064 nm Nd-YAG Laser Deposition of Titanium on Silicon in a Nitrogen Environment - Amistoso, Jose Omar; Pabit, Edgardo; Hui, Marilyn; Garcia, Wilson (Science Diliman: A Journal of Pure and Applied Sciences; Vol 11 No 2 (1999), 2007)
Pulsed laser deposition (PLD) technique was demonstrated for the deposition of titanium nitride (TiN) thin films on Si (100) substrates. A 1064 nm pulsed Nd-YAG laser is focused on a titanium (99.5%) target in a nitrogen environment to generate the atomic flux needed for the film deposition. Spectroscopic analysis of the plasma emission indicates the presence of atomic titanium and nitrogen, which are the precursors of TiN. Images of the films grown at different laser pulse energies show an increase in the number and size of deposited droplets and clusters with increasing laser pulse energy. A decrease in cluster and droplet size is also observed, with an increase in substrate temperature. EDS data show an increase in the titanium peak relative to the silicon as the ambient nitrogen pressure is decreased. An increase in deposition time was found to result in large clusters and irregularly shaped structures on the substrate. Post-deposition annealing of the samples enhanced the crystallinity of the film.
Keywords: laser deposition; titanium nitride; laser-induced plasma